(3ebOeI aj ahGFO TQjaI hbhGYO dWjaI aj eYQaI GUWdGMGJ GdbGehSs - (3GdhaGFj GdghQjfj GdCMeOj GdCRgQj GdCTYQj GdMfaj GdTGaYqj, CHh GdhaGA, , fUQ Hf fUQ jhfS, J (B1291 (3g`s ((3ecI GdecQeIs)
(3ChdgG (B:s
(3GdMeO ddg GdPj LYd dZI GdYQH CTQa GddZGJ (B.. (3agPg KeQGJ GbJWagG (B.. (3deYQaI cjajI eQGLYI GdbGehS ef MGTjJg ddYdGeI (B.. (3eMeO Hf GdWjH (B((3GdaGSj(B) (3hdjS dj ajgG EdG eLQO GdLeY ef CHhGH eJaQbI (B..s
(3BNQgG (B:s
.. (3hZjQ GdYhV jbY HYO GdQaY fMh TJGf eG RjO hYeQh hbhdg dh HGHGfjf LGA jNWHgG QeO eG Cfa NGWH HOe , bhdg QeO eG Cfa cPG aj GdfSN haj fSNI GdTGQM VQL (B.(3Cg`s
(3JHUQI GdYfhGf (B:s
(3ebJWaGJ ef MGTjI GdYdGeI eMeO Hf GdWjH GdaGSjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B8\29s
(3GdCYdGe (B8\29s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GddZIs